2016
DOI: 10.3390/ijfs4030015
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future Betas: Empirical Asset Pricing of US and Southeast Asian Markets

Abstract: Abstract:The study adds an empirical outlook on the predicting power of using data from the future to predict future returns. The crux of the traditional Capital Asset Pricing Model (CAPM) methodology is using historical data in the calculation of the beta coefficient. This study instead uses a battery of Generalized Auto Regressive Conditional Heteroskedasticity (GARCH) models, of differing lag and parameter terms, to forecast the variance of the market used in the denominator of the beta formula. The covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A shorter 90-day estimation horizon from t −111 to t −21 days before the event ( t 0 ) was used, as past studies had found that forecasting performance in the smaller more volatile markets of Asia performed best with less historical in-sample data (not more) (French, 2016a; French, 2016b). The nature of markets change, as they also have in the USA and Europe, the in-sample properties would not remain constant.…”
Section: Methodsmentioning
confidence: 99%
“…A shorter 90-day estimation horizon from t −111 to t −21 days before the event ( t 0 ) was used, as past studies had found that forecasting performance in the smaller more volatile markets of Asia performed best with less historical in-sample data (not more) (French, 2016a; French, 2016b). The nature of markets change, as they also have in the USA and Europe, the in-sample properties would not remain constant.…”
Section: Methodsmentioning
confidence: 99%